Factors Affecting Social And Environmental Accounting Reviewed On Accounting Students' Academic Fraud From The Fraud Hexagon Perspective - Firdaus Wandy Agustan; Wayhuni , Wayhuni (CV. AFDIFAL MAJU BERKAH, 2024)
The complexity of factors influencing academic cheating in the specific context of social and environmental accounting. The implication is the importance of developing educational strategies, supervision and an academic culture with integrity to prevent and reduce fraud in the educational environment, especially in the Accounting Study Program, as well as to identify factors that influence the tendency of academic fraud in the academic environment, especially from the Fraud Hexagon perspective. This study takes a quantitative approach by using a questionnaire as an instrument for collecting data from a sample of accounting study program students. Factors considered include pressure, opportunity, rationalization, selfish ability and collusion. The research results show that high academic pressure, easy opportunities to cheat, and supportive rationalization are significant factors in influencing academic cheating behavior among accounting students. Meanwhile, individual ego and collusion were not proven to have a significant influence in the context studied. The implications of this research are the need to improve supervision during exams, strengthen ethical values ​​in the educational curriculum, and provide students with a better understanding of the consequences of academic cheating behavior. It is hoped that this study can contribute to the development of more effective strategies for preventing and managing the risk of academic fraud in higher education institutions.